Implementation of Automated Criminal Face Detection System Using Facial Recognition Approach - Jebasheeli, V; Vadivel, R (International Journal of Computer Sciences and Engineering, 2020)
Criminal records usually contain personal information about a particular person and image. To identify any criminal, require an identity document in person, provided by eyewitnesses. In many cases the quality and resolution of parts of the recorded images is poor and difficult to detect. Identification can be done in many ways such as finger print, eyes, DNA etc. One of the programs is facial recognition. Although the ability to use intelligence or character in suspicious facial expressions, one's ability to recognize faces is amazing. Criminal records usually contain personal information about a particular person and image. The identification of any criminal requires specific identification in relation to a particular person or persons, provided by eyewitnesses. Based on the information provided by eyewitnesses, this investigation will be conducted. In many cases the quality and resolution of parts of the recorded images is poor and difficult to detect. In this paper, it is divided into the performance of graphical images in three stages; low, medium and high level to process and analyze a given face. This paper demonstrates better results than the conventional methods associated with the face recognition process used in crime detection.